Correlation between Right Ventricular Function with Revascularization Time and 30-day Mortality in ST-Elevation Myocardial Infarction Patients Underwent Right Coronary Artery Intervention - Marshell Luntungan; Dewi U. Djafar; Agnes L. Panda; Agustinus M. Sarayar; Filipus M. Yofrido (e-CliniC, 2022)
Abstracts: Right ventricular (RV) function provides strong prognostic information in patients treated with primary percutaneous coronary intervention (PCI) due to myocardial infarction. Longitudinal RV systolic function can be assessed by the measurement of the tricuspid annular plane systolic excursion (TAPSE). This study aimed to evaluate the correlation between TAPSE and revascularization time with 30-day mortality using TIMI risk score in patients presenting STEMI who underwent revascularization of right coronary artery (RCA). This was a descriptive amd analytical study. Data were collected from iSTEMI Registry database which consisted of 49 STEMI patients undergoing PCI in RCA and TAPSE measurement at Prof. Dr. R. D. Kandou General Hospital from October 3rd, 2018 to July 28th, 2019. Echocardiographic examination was done within 48 hours of hospitalization. A descriptive analysis and bivariate correlation with Spearmanâ€™s rho were applied between given variables. P-value of <0.05 was considered to be statistically significant. The results showed that the mean age of the patients was 57.92 10.345 years old and 79.2% were male. The mean TAPSE measurement was 18.51 mm +/- 3.63 mm. The median revascularization time was 357.5 minutesÂ  while median TIMI score was 4. Shorter treatment time (p=0.708) and lower TIMI score (p=0.923) were not associated with better right ventricular function measured with TAPSE in patients undergoing RCA intervention. In conclusion, right ventricular function is not associated with revascularization time and thirty days mortality in patients presenting with ST-elevation acute myocardial infarction involving right coronary artery.Keywords: tricuspid annular plane systolic excursion; revascularization time; right coronary artery; ST-elevation myocardial infarction